2013
DOI: 10.1523/jneurosci.2268-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Vergence Neurons Identified in the Rostral Superior Colliculus Code Smooth Eye Movements in 3D Space

Abstract: The rostral superior colliculus (rSC) encodes position errors for multiple types of eye movements, including microsaccades, small saccades, smooth pursuit, and fixation. Here we address whether the rSC contributes to the development of neural signals that are suitable for controlling vergence eye movements. We use both single-unit recording and microstimulation techniques in monkey to answer this question. We found that vergence eye movements can be evoked using microstimulation in the rSC. Moreover, among the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 50 publications
4
43
0
Order By: Relevance
“…However, there is some evidence from work in cats that the rostral superior colliculus might modulate lens accommodation (Ohtsuka and Sato 1997; Ohtsuka and Nagasaka 1999). More recently, stimulation of the rostral pole of the superior colliculus was shown to modulate vergence movements in monkeys (Chaturvedi and Van Gisbergen 2000) and cells whose activity is modulated with respect to vergence eye movements have been recorded (Van Horn et al 2013). In addition, pupillary dilation has been recorded following electrical stimulation of the superior colliculus (Wang et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is some evidence from work in cats that the rostral superior colliculus might modulate lens accommodation (Ohtsuka and Sato 1997; Ohtsuka and Nagasaka 1999). More recently, stimulation of the rostral pole of the superior colliculus was shown to modulate vergence movements in monkeys (Chaturvedi and Van Gisbergen 2000) and cells whose activity is modulated with respect to vergence eye movements have been recorded (Van Horn et al 2013). In addition, pupillary dilation has been recorded following electrical stimulation of the superior colliculus (Wang et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A complementary, yet unidentified, pathway likely provides a strabismus signal to the lateral rectus muscle. Recent studies in normal monkeys have suggested that the rostral superior colliculus plays a part in vergence eye movements, and a pathway from the rostral superior colliculus to the abducens nucleus has been hypothesized as providing a slow vergence signal to the LR muscle (Van Horn et al 2013). This pathway could potentially provide the strabismus signal to the LR muscle.…”
Section: What Factors Govern Eye Misalignment and Disruption Of Eymentioning
confidence: 99%
“…In monkey only injections into the ventral pretectum including the deep layers of the rostral superior colliculus (SC) gave rise to strong anterograde labeling in the LVC, AM, SOA with EWpg, and the C group (B€ uttner-Ennever et al, 1996). This projection may originate from vergence-related neurons in the pretectum (Judge and Cumming, 1986) or from the rostral SC, which is important for eye fixation (Suzuki et al, 2004;van Horn et al, 2013). In monkey and cat, the rostral SC contains neurons whose activity is linked to vergence (van Horn et al, 2013) and accommodation (Suzuki et al, 2004), indicating a role in the linkage of fixation, accommodation, and vergence as required for aligning the eyes during fixation on a visual target.…”
Section: Pretectummentioning
confidence: 99%